Inhaling habits among smokers of different types of cigarette. - Wald, N; Idle, M; Boreham, J; Bailey, A (1980)
Inhaling habits were studied in 1316 men who freely smoked their usual brands of cigarette. An index of inhaling was calculated for each person by dividing the estimated increase in carboxyhaemoglobin level from a standard number of cigarettes by the carbon monoxide yield of the cigarette smoked. Smokers of ventilated filter cigarettes inhaled 82% more than smokers of plain cigarettes (p less than 0.001) and those who smoked unventilated filter cigarettes inhaled 36% more (p less than 0.001). Cigarette consumption was similar among smokers of each type of cigarette. Assuming that the intake of tar and nicotine is proportional to the inhaling index, the intake in either group of filter cigarette smokers would have been less than that in plain cigarette smokers. Among smokers of unventilated cigarettes, however, the intake would not have been much less.